PEDULI PENDIDIKAN ANAK JALANAN BERSAMA SAHABAT GROGOL - Nathania, Janice; Wijoyo, Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This paper investigates the vital role of education in improving the well-being of street children, with a focus on enhancing their educational opportunities and outcomes. Street children, who are frequently marginalized and disregarded, encounter a range of obstacles that impede their access to high-quality education, including financial constraints, societal biases, and a lack of formal identification. The paper delves into the various challenges faced by street children, including economic limitations, social prejudices, and the absence of formal identification. The central message conveyed is that collaborative initiatives between Sahabat Grogol and Tarumanagara University aim to enhance educational accessibility. This is realized through the implementation of several activities in early childhood education institutions, such as introducing letters and numbers, fostering literacy skills, engaging in creative tasks like decorating doughnuts, and participating in physical exercises. The implementation method of the Community Service Program (PKM) involves face-to-face interactions and demonstrates results that have an impact on street children, such as the ability to read, write, improve motor skills, and enhance creativity. Furthermore, the paper underscores the substantial role these children play in contributing meaningfully to society. By investing in education and promoting collective efforts, the objective is to empower street children to construct a more promising and sustainable future for themselves.